2016
DOI: 10.1016/j.cub.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Transmission of Social Roles Drives Resilience to Poaching in Elephant Networks

Abstract: Network resilience to perturbation is fundamental to functionality in systems ranging from synthetic communication networks to evolved social organization [1]. While theoretical work offers insight into causes of network robustness, examination of natural networks can identify evolved mechanisms of resilience and how they are related to the selective pressures driving structure. Female African elephants (Loxodonta africana) exhibit complex social networks with node heterogeneity in which older individuals serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 29 publications
4
96
0
Order By: Relevance
“…For example, a recent observational study indicated that wild African elephant ( Loxodonta africana ) populations maintain their social network structure, despite ivory poaching eliminating the highly connected nodes (i.e. older female elephants) [58]. While no active response to such loss was exhibited, the robustness instead stemmed from daughters replicating their mothers' social positions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent observational study indicated that wild African elephant ( Loxodonta africana ) populations maintain their social network structure, despite ivory poaching eliminating the highly connected nodes (i.e. older female elephants) [58]. While no active response to such loss was exhibited, the robustness instead stemmed from daughters replicating their mothers' social positions.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial and social relationships of bears are likely to change more rapidly in areas with higher hunting mortality, thereby potentially decreasing the cohesion of their social network2829 but see ref. 30. Such effects could also influence the female reproductive rate because female brown bears exhibit kin-related spatial structures31, where neighbors negatively affect each other’s probability of having cubs3233.…”
Section: Discussionmentioning
confidence: 99%
“…Movement decisions are guided not only by food availability, but also by perceived risks (Graham, Douglas-Hamilton, Adams, & Lee, 2009), water availability (Chamaillé-Jammes et al, 2009, and social companions (Goldenberg, Douglas-Hamilton, & Wittemyer, 2016), among other factors. Rather, elephants utilize established home ranges and move seasonally to maximize resource availability.…”
Section: Discussionmentioning
confidence: 99%